Scaling MongoDB - Chodorow, Kristina (O'Reilly Media, 2011)
Create a MongoDB cluster that will to grow to meet the needs of your application. With this short and concise book, you'll get guidelines for setting up and using clusters to store a large volume of data, and learn how to access the data efficiently. In the process, you'll understand how to make your application work with a distributed database system. Scaling MongoDB will help you:Set up a MongoDB cluster through shardingWork with a cluster to query and update dataOperate, monitor, and backup your clusterPlan your application to deal with outagesBy following the advice in this book, you'll be.